The polictical economy informed lobbies - Lima, Rafael Coutinho Costa (2005)
We analize a discrete type version of a common agency model with informed principals of Martimort and Moreira (2005) in the context of lobby games. We begin discussing issues related to the common values nature of the model, i.e.the agent cares directly about the principal’s utility function. With this feature the equilibrium of Martimort and Moreira (2005) is not valid. We argue in favor of one solution, although we are not able to fully characterize the equilibrium in this context. We then turn to an application: a modification of the Grossman and Helpman (1994) model of lobbying for tariff protection to incoporate assimetric information (but disconsidering the problem of common values) in the lobbies objective function. We show that the main results of the original model do not hold and that lobbies may behave less agressively towards the police maker when there is private information in the lobbies valuation for the tariffs.